Business Development Strategy of Instant Ginger Start-Up in The Covid-19 Pandemic - Dzulfikar, Arif; Jahroh, Siti; Ali, Mochammad Mukti (School of Business, Bogor Agricultural University (SB-IPB), 2022)
COVID-19 has changed people's lifestyles and transaction behavior. People switch to a healthier lifestyle and use digital marketing for daily transactions. Arvan Natural Group, a start-up company that produces ginger powder, must be able to optimize these opportunities. The increment of a competitor in the health drink sector has even tighter competition. In addition, this company faces several problems regarding raw materials (continuity and quality), product development, and limited channels. Therefore, this study aims to identify existing business models, develop alternative strategies, prioritize business strategies, and build a new business model. The data processing technique thoroughly analyzes BMC, SWOT, IFE/EFE, and QSPM. Experts working in biopharmaceutical research and business give the weights and ratings. IE matrix showed the company's position is in quadrant II (2.92, 3.02). It is categorized as grow and build strategy. Based on QSPM analysis, strategies classified as high urgency and plotting in the new business model are expanding channels (strategic location, reseller system), adding advertisement budget and joining promotion events, and applying for bonus promotion. Besides, there are differentiating products, creating an operational partnership system with farmers, improving marketing content (video), applying the functional structure of human resources, and creating product size variety. Keywords: BMC, digital marketing, lifestyle, QSPM, SWOT